Effect of composite shade, curing time and mode on temperature rise of silorane and methacrylate- based composite resins - Sayed Mostafa Mousavinasab; Arman Salehi; Negar Salehi (Babol University of Medical Sciences, 2016)
Introduction: The present study was performed to evaluate the effects of light-curing modes and shades of methacrylate and silorane-based composite resins on temperature rise during polymerization of composite resins. Materials &Methods: In this in vitro study, ninety composite samples with two types of composite resin - methacrylate-based and a low-shrinkage silorane-based were prepared, in 3 groups (30 samples in each group), Group 1: Filtek Z250 (shade A3), Group 2: Filtek Z250 (shade B2) and Group 3: Filtek P90 (shade A3). To evaluate temperature changes, 15 samples and the other half were light-cured using the standard and soft start curing modes for 40 seconds, respectively. A k-type thermocouple was used to recorded temperature changes. Results: Temperature rise in the silorane-based composite resin group (group 3) was higher than that in the methacrylate-based one (group 1) (P<0.001). Temperature rise with the darker shade (group 1) was higher than that with lighter shade (group 2) (P<0.001). Standard curing resulted in more temperature rise compared to soft start curing; however, the difference was only significant in group 2 (P<0.001). In all groups, temperature increased with an increase in curing time and the temperature rise pattern during the first 10 seconds with the soft start curing was not consistent with the standard curing (in group 2 and 3); the temperature rise pattern was milder than the soft start curing (P<0.001). Conclusion: Factors such as composite resin type, shade and curing mode affected temperature changes in composite resins evaluated in the present study.